Measurement of W±W± vector-boson scattering and limits on anomalous quartic gauge couplings with the ATLAS detector - Aaboud, M. (2016)
This paper presents the extended results of measurements of W±W± j j production and limits on anomalous quartic gauge couplings using 20.3 fb−1 of proton–proton collision data at √ s = 8 TeV recorded by the ATLAS detector at the Large Hadron Collider. Events with two leptons (e or µ) with the same electric charge and at least two jets are analyzed. Production cross-sections are determined in two fiducial regions, with different sensitivities to the electroweak and strong production mechanisms. An additional fiducial region, particularly sensitive to anomalous quartic gauge coupling parameters α4 and α5, is introduced, which allows more stringent limits on these parameters compared to the previous ATLAS measurement.